The Role of Buddhist Cultural Spaces in Promoting Sustainable Tourism: A Case Study in Vietnam - Ha, Duong Thi Thu (Journal of Ecohumanism, 2024)
The aim of this study is to explore the role of Buddhist space in sustainable tourism development. This research study was conducted on Buddhist cultural hubs of sustainable tourism into the Buddhist relic sites in Hanoi and those of the northern provinces of Vietnam. The hypotheses were tested using regression analysis to prove that cultural preservation, environmental awareness, support and consideration of the community, ethical tourism practices, and sustainable engagement of the visitors strongly hinted toward a direct impact on sustainable tourism. The findings reveal that Buddhist cultural sites are instrumental in integrating cultural preservation, environmental upkeep, and ethical tourism practices with prolonged visitor engagement. Further implications would guide the policymakers and tourism stakeholders on how to carve out an ideal development plan to conserve the cultural and environmental reserves while taking sustainable tourism development forward. This study provides a framework for balancing growth in tourism with the conservation of Vietnam’s cultural heritage and natural resources.